2022
DOI: 10.48550/arxiv.2210.01285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrino-induced coherent $π^{+}$ production in C, CH, Fe and Pb at $\langle E_ν\rangle \sim 6$ GeV

Abstract: MINERvA has measured the νµ-induced coherent π + cross section simultaneously in hydrocarbon (CH), graphite (C), iron (Fe) and lead (Pb) targets using neutrinos from 2 to 20 GeV. The measurements exceed the predictions of the Rein-Sehgal and Berger-Sehgal PCAC based models at multi-GeV νµ energies and at produced π + energies and angles, Eπ > 1 GeV and θπ < 10 • . Measurements of the cross-section ratios of Fe and Pb relative to CH reveal the effective A-scaling to increase from an approximate A 1/3 scaling at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Finally, MINER𝜈A has completed a measurement of coherent pion production 𝜈 ℓ + 𝐴 → ℓ − + 𝜋 + + 𝐴, first observed in [17], for the ME beam and, for the first time, in the passive nuclear targets [18]. The analysis is crucial for differentiating between different models of the coherent cross section, which generally predict different dependences on nuclear mass number.…”
Section: Miner𝜈a Medium-energy Physics Resultsmentioning
confidence: 99%
“…Finally, MINER𝜈A has completed a measurement of coherent pion production 𝜈 ℓ + 𝐴 → ℓ − + 𝜋 + + 𝐴, first observed in [17], for the ME beam and, for the first time, in the passive nuclear targets [18]. The analysis is crucial for differentiating between different models of the coherent cross section, which generally predict different dependences on nuclear mass number.…”
Section: Miner𝜈a Medium-energy Physics Resultsmentioning
confidence: 99%
“…Those models have since been improved to agree better with the MINERvA low energy results, and are currently in use by the community. MINERvA has measured the A-dependence of coherent charged current pion production [16] and has demonstrated that although the pion energy spectrum for carbon (now) matches the models on the market reasonably well, neither the spectrum on iron or lead is well modeled, where the discrepancy with the model grows with atomic number. For neutrino energies above 10 GeV, the A-scaling is consistent with A 2/3 for both iron and lead, for lower neutrino energies the A-scaling is significantly below A 2/3 , where for iron it is consistent with A 1/3 scaling.…”
Section: Coherent Pion Productionmentioning
confidence: 99%